OFFICE BUILDING DESIGN WITH A METAPHORICAL APPROACH IN PULO GADUNG – EAST JAKARTA PERANCANGAN GEDUNG PERKANTORAN DENGAN PENDEKATAN METAFORA - Gerie Munggaran; Elly Cornelies; RizKi Hambali (RANGKIANG: Jurnal Pengabdian Pada Masyarakat, 2024)
ABSTRACTEtymologically, metaphorical terminology is formed through the combination of two Greek words, namely "meta" (above) and "pherein" (transfer). In Modern Greek, the word metaphor also means "transfer" or "transport". Thus, metaphor is the transfer of the image, meaning, or quality of an expression to another expression, Metaphor is an approach in architecture that has a concept as an idea and the result is a meaning that is concretely revealed or abstract from the designer to the user or actor of the building so that it has a connotative meaning in addition to its main function as a building by using abstract metaphors, combination metaphors, metaphorsKeywords: abstract metaphors,combination metaphors,metaphors